SOCS1: a host factor required for HIV-1 Gag trafficking. (May 2008) - Sivakumaran, Haran; Harrich, David
Evaluation of: Ryo A, Tsurutani N, Ohba K et al. : SOCS1 is an inducible host factor during HIV-1 infection and regulates the intracellular trafficking and stability of HIV-1 Gag. Proc. Natl Acad. Sci. USA 105, 294––299 (2008). Gag is an essential HIV protein that is responsible for assembling infectious viral particles. The journey of Gag from synthesis to virion formation is an attractive target for anti-HIV therapy. While a lot is known about the cellular factors required for virion assembly and budding, relatively little is known about factors required for Gag trafficking. Ryo and colleagues provide the first evidence of such a factor, the suppressor of cytokine signaling (SOCS)1. They demonstrated that SOCS1 is important for Gag stability and plays a critical role in its trafficking within the cell. Without SOCS1 Gag accumulates in perinuclear bodies and is degraded by lysosomes. This article therefore highlights a new and novel target for stopping the production of HIV, a target that belongs to the relatively invariant host rather than the rapidly evolving virus.